2007
DOI: 10.2967/jnumed.106.039107
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Diagnostic Accuracy of a Gated SPECT Early-Imaging Protocol: A Multicenter Study of the Myoview Imaging Optimization Group

Abstract: The aim of this study was to investigate whether early (time 1, or T1) myocardial tetrofosmin imaging is feasible and as accurate in detecting coronary artery disease as is standard delayed (time 2, or T2) imaging. Methods: One hundred twenty patients (100 men and 20 women; mean age 6 SD, 61 6 10 y) with anginal symptoms underwent tetrofosmin gated SPECT. Stress/rest T1 imaging was performed at 15 min and T2 at 45 min after injection. Image quality was visually evaluated using a 4-point scale (from 0 5 poor to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 14 publications
5
38
0
3
Order By: Relevance
“…Finally, Giorgetti et al [22] have found differential wash-out of Tc-tetrofosmin from normal versus ischemic myocardial regions advocating a short interval from injection to SPECT scanning, whereas we used a 45-60 minutes interval (according to EANM guidelines [7] …”
Section: Discussionmentioning
confidence: 99%
“…Finally, Giorgetti et al [22] have found differential wash-out of Tc-tetrofosmin from normal versus ischemic myocardial regions advocating a short interval from injection to SPECT scanning, whereas we used a 45-60 minutes interval (according to EANM guidelines [7] …”
Section: Discussionmentioning
confidence: 99%
“…One can shorten the dual study by performing a 15-min renal acquisition during a gated SPECT fast imaging protocol (15). Cardiorenal scintigraphy with 99m Tc-tetrofosmin may thus be proposed especially in those patients undergoing gated SPECT in whom a significant risk of overt or subclinical renal disease exists.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with 99m Tc-sestamibi, 99m Tc-tetrofosmin is cleared more quickly from both lungs and liver, allowing earlier imaging (12)(13)(14)(15) as is widely used in gated SPECT.…”
mentioning
confidence: 99%
“…This was followed by acquisition of rest MPI with the identical acquisition protocol several minutes 6 [14] after administration of a three times higher dose of 99m Tc-tetrofosmin (955±169 MBq). MPI scans were acquired using a multipinhole collimator (effective diameter aperture of 5.1 mm) and 19 stationary detectors simultaneously imaging 19 different views of the heart as previously reported.…”
Section: Image Acquisitionmentioning
confidence: 99%